2015
DOI: 10.1097/md.0000000000002238
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of the Sirtuin 1 (SIRT1) Gene are Associated With age-Related Macular Degeneration in Chinese Han Individuals

Abstract: To investigate whether 3 variants in sirtuin 1 (SIRT1) gene contributed differently in patients with age-related macular degeneration (AMD) in a Chinese Han population.We conducted a case–control study in a group of Chinese patients with AMD (n = 253) and contrasted the results against a control group (n = 292). Three single nucleotide polymorphisms (SNPs) of SIRT1 gene including rs12778366, rs3740051, and rs4746720 were genotyped using improved multiplex ligase detection reaction. The association between targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
8
0
2
Order By: Relevance
“…Therefore, further studies are needed to Although SIRT1 is expressed in all trophoblast layers of the placenta and is important for proper trophoblast differentiation and placental development [43], the relationship between LPS-associated placental inflammation and SIRT1 expression has not been studied previously. Recent studies showed that single nucleotide polymorphisms (SNPs) in the SIRT1 gene are associated with carotid atherosclerosis, major depressive disorder, age-related macular degeneration, and severe obesity [44][45][46][47]. However, it is not known whether SNPs in the SIRT1 gene have an influence on the NLRP3 inflammasome-mediated inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies are needed to Although SIRT1 is expressed in all trophoblast layers of the placenta and is important for proper trophoblast differentiation and placental development [43], the relationship between LPS-associated placental inflammation and SIRT1 expression has not been studied previously. Recent studies showed that single nucleotide polymorphisms (SNPs) in the SIRT1 gene are associated with carotid atherosclerosis, major depressive disorder, age-related macular degeneration, and severe obesity [44][45][46][47]. However, it is not known whether SNPs in the SIRT1 gene have an influence on the NLRP3 inflammasome-mediated inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology and risk factors of AMd are complex (40). chen et al (41) investigated three variants of the SIRT1 gene associated with AMd in chinese Han individuals, and identified that the rs12778366 polymorphism within the promoter region of SIRT1 was significantly associated with AMd in recessive and codominant models. Expression of SIRT1 was more frequent in RPE and vascular endothelial cells (VEcs) in human cNV membranes (42).…”
Section: Sirt1 and Age-associated Macular Degenerationmentioning
confidence: 99%
“…However, one study suggested that genetic variations of SIRT1 could be implicated in the pathophysiology of AMD in the Chinese Han population. 115 Another study indicated that lower expressions of SIRT1 and PGC1α were observed in iPSC-derived RPE cells from patients with AMD. 116 Even less data exist for AMPK and AMD—a few reports suggested AMPK and mechanistic target of rapamycin (mTOR) as potential therapeutic targets in AMD, 117 , 118 while in vitro experiments suggested a protective effect for AMPK activation on RPE cells and downregulation of complement factor B (unpublished data, Eun Jee Chung et al).…”
Section: Aging and Senescencementioning
confidence: 99%